The Association of the R563Q Genotype of the ENaC With Phenotypic Variation in Southern Africa - Jones, Erika S.W.; Owen, E. Patricia; Rayner, Brian L. (American journal of hypertension, 2012)
Background The epithelial sodium channel (ENaC) may be a common underlying pathway for the development of primary hypertension. In South Africa, the R563Q variant of the ENaC is associated with low-renin-low-aldosterone hypertension and preeclampsia in black Africans and mixed-ancestry peoples. The purpose of this study was to investigate the prevalence of the R563Q variant in the multiethnic populations of South Africa, its association with hypertension and response to amiloride in patients with resistant hypertension. Methods Samples were obtained from hypertensives and normotensive controls in Cape Town and Johannesburg, and unselected San living in the rural areas of the Northern Cape and Namibia. Resistant hypertensives with the R563Q variant were treated with amiloride. Results One thousand nine hundred and thirty nine (1,468 hypertensives, 471 controls) subjects were recruited. Eighty-seven (5.9%) of the hypertensives were R563Q heterozygote vs. 8 (1.7%) of the normotensives (P < 0.0005). In the Namibian and Northern Cape San 19.5% and 18.8% of subjects were R563Q positive. There was no association with hypertension. Spot sodium excretion was lower in the San compared to urban subjects (7.3 vs. 12.2 mmol/mmol, P = 0.016). Twenty-two R563Q heterozygote patients with resistant hypertension received amiloride with a mean reduction in blood pressure (BP) of 36/17 mm Hg (P < 0.0001). Conclusions The R563Q variant is strongly associated with hypertension in urban areas in South Africa. The San are the likely origin of the variant, but it is not associated with hypertension, presumably due to their lower sodium intake. Screening patients with resistant hypertension in South Africa for the R563Q variant provides a feasible pharmacogenetic approach to treatment.